Development of the scale for attitude toward new foods - Ozgen, Leyla; Benli, Mehlika; Turkmen, Fatih (Progress in Nutrition, 2019)
Aim: This study aimed to develop an instrument to assess consumer attitude toward new foods. Methods: This was a descriptive study. The five-point Likert-type scale comprised three subscales and 25 items. In the study, the “Demographic Information Form,” the “Scale for Attitude toward New Foods” (SATNF) and the “Innovativeness Scale” (IS) were used as data collection instruments. Study group: The study sample comprised 300 respondents selected with convenience sampling. The results of the factor analysis performed to test construct validity yielded item factor loadings varying between 0.32 and 0.70 while Cronbach’s alpha values for the skepticism, innovativeness and traditionalism subscales were computed as 0.74, 0.80 and 0.72, respectively. The applicability of factor analysis to the data structure was tested with a Kaiser-Meyer-Olkin test (0.76) and a Bartlett’s test of sphericity (X2 = 1855.123; p<0.000). Results and Discussion: The findings indicated that the scale was a valid and reliable construct. The study results revealed significant differences in the skepticism subscale by gender, marital status and attention to brand, food label and nutrition content. Innovativeness scores of the respondents who were attentive to nutrition content when tasting new foods were found to be higher than those who were not attentive. In addition, married respondents had a higher mean score in the traditionalism subscale compared to unmarried respondents. Conducting further validity and reliability studies for the Scale for Attitude toward New Foods at different times would help the scale become a more valid and reliable instrument. The researchers recommend investigating attitude toward new foods among individuals living at coastal and inland areas and examining the differences between the subscales in future studies on the subject. This study has some limitations. The greater number of female respondents in comparison to male respondents and the fact that most of the respondents did not complete and return the questionnaire forms while some respondents even submitted incomplete forms are among these limitations.